ANALYSIS OF LEARNING NEEDS OF ADVANCED GRADE STUDENTS IN BIPA CONVERSATION LEARNING DESIGN - Khairunnisa; Nasution, Jamaluddin; Eka Dewi Siswati; Rumindah; Danik Budianti; Pujiyanti (Institut Agama Islam Negeri (IAIN) Palopo, 2025)
Abstract This study aims to analyze the learning needs of advanced learners (KL) in order to design effective and contextual Indonesian for Foreign Speakers (BIPA) learning conversations. KL learners generally have mastered the basics of language, so learning at this level needs to focus on developing more functional and applicable language skills, especially in the context of everyday and professional communication. This study uses a qualitative descriptive method with a needs analysis approach through the analysis of advanced BIPA learning materials. The results show that learners need conversation materials that are relevant to their social and work environments, such as interactions in the workplace, public services, and intercultural communication. Based on these findings, a BIPA conversation learning design was prepared based on the context and needs of learners. This design is expected to increase learning effectiveness and provide a meaningful learning experience and in accordance with the real communication goals of advanced BIPA learners. Keywords : BIPA, learning needs, advanced classes, conversation, learning design